1994
DOI: 10.1507/endocrj.41.361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Estrogen Treatment in Female Patients with Dementia of the Alzheimer Type.

Abstract: Abstract. This study was designed to investigate the therapeutic efficacy of estrogen in female patients with dementia of the Alzheimer type (DAT). Fifteen DAT patients with a mean age of (x ± SE) 71.9 ± 2.4 years were treated with 0.625 mg of conjugated equine estrogens orally twice a day for 6 weeks. Of the 15 DAT patients, 4 were diagnosed as mild, 7 as moderate and 4 as severe. The effects of estrogen on DAT patients were evaluated by psychometric assessments, behavior rating scales, regional cerebral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(111 citation statements)
references
References 36 publications
3
98
0
8
Order By: Relevance
“…Consistent with previous reports (Ohkura et al, 1994;Hogervorst et al, 2002), we found an improved cognitive function in menopausal women after HRT. Recent animal studies have suggested biologic mechanisms through which estrogen may maintain neuronal function (Dubal and Wise, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports (Ohkura et al, 1994;Hogervorst et al, 2002), we found an improved cognitive function in menopausal women after HRT. Recent animal studies have suggested biologic mechanisms through which estrogen may maintain neuronal function (Dubal and Wise, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Many clinical studies have supported the therapeutic effect of estrogen on AD, since Fillit et al [20] first reported an open trial of estradiol-17b (E 2 ) therapy for AD (Table 2) [20][21][22][23][24][25][26][27][28][29][30][31][32]. However, the therapeutic effect was not established.…”
Section: ) Therapeutic Effect Of Estrogenmentioning
confidence: 99%
“…19,20) Epidemiological evidence supports the notion that estrogen replacement therapy can be used to effect a reduction in the incidence of AD in post-menopausal women, 21) and several clinical trials have reported that estrogen therapy improves cognitive functioning in patients who suffer from AD. 22,23) Estrogen causes an increase in ChAT activity in the specific basal forebrain nuclei and projection areas of female rats. 24) The cell bodies of the ACh-containing neurons are known to be principally situated in the basal forebrain, and have been demonstrated to transmit ACh to the cortical and hippocampal regions, as well as to the amygdale.…”
Section: Resultsmentioning
confidence: 99%
“…Male ICR mice (Samtaco BioKorea, Seoul, Korea), weighing 25-30 g, were used in passive avoidance and Y-maze tests after a one-week adaptation period (20)(21)(22)(23) C; 12 h light cycle from 09:00 to 21:00; food, Agribrand Purina Korea, and water ad libitum). The experimental procedures were approved by the guidelines established by the Animal Care and Use Committee at Korea University.…”
Section: Methodsmentioning
confidence: 99%